Rolled Tendon Allograft Interposition Arthroplasty for Salvage Surgery of the Hallux Metatarsophalangeal Joint. (April 2018) - Thomas, Danielle; Thordarson, David
Background: Hallux rigidus is a common osteoarthritic disease of the first metatarsophalangeal joint (MTPJ). Few salvage treatment options exist that preserve motion for patients who have failed an initial procedure and who are not amenable to fusion, typically patients who are active or who would like to wear high heels. Allograft tendon interpositional arthroplasty is an unconventional salvage treatment option that may preserve motion and prevent bone loss. Methods: A retrospective chart review is reported of 19 patients who failed previous procedures and refused fusion who underwent allograft tendon interpositional arthroplasty of the hallux MTPJ by a single surgeon between 2012 and 2015. Outcomes included the American Orthopaedic Foot & Ankle Society (AOFAS) hallux metatarsophalangeal-interphalangeal scale assessment as well as measurement of apparent joint space on anterior to posterior and lateral views. Results: The cumulative average AOFAS score for all patients was 68.5 preoperatively and 74.1 postoperatively. The average AOFAS pain subscore was 24.7 preoperatively and 26.8 postoperatively (SD = 7.7 and 13.8, respectively). Radiographically, patients had an increase in apparent joint space from pre- to postoperatively, most notable on the lateral view (0.6 to 4.7 mm; SD = 0.7 and 3.2 mm). Five patients required a second operative procedure, for an overall 26% reoperation rate. One patient underwent hallux MTPJ fusion after the interpositional arthroplasty. An additional 4 patients (21%) had symptoms requiring a steroid injection, and another 3 patients (16%) were recommended to undergo a revision procedure based on their symptoms. Conclusion: Rolled allograft tendon interposition arthroplasty performed poorly as a salvage strategy for failed previous hallux MTPJ surgery for hallux rigidus because of a high rate of complication and minimal benefits. The senior author has abandoned the technique. Level of Evidence: Level IV, retrospective case series.